Perencanaan Strategis Menuju Webometrics dan 4ICU Pada Website Perguruan Tinggi - Kurniawijaya, Putu Andhika; Wiharta, Dewa Made; Sastra, Nyoman Putra (Majalah Ilmiah Teknologi Elektro, 2019)
The most frequently used instrument by College Indonesia nor the world as reference materials to evaluate performance and productivity based on website is through the database of appraisers, including World University namely Webometrics and 4ICU. There are a number of differences regarding the indicators used by the two ranking databases. The difference was certainly potent determination of ranking colleges that are also different. The purpose of this study is to devise a strategic plan policy that is capable of being a guide for local colleges in improving its quality to global competition. Based on the results of the calculation Spearman Rank, then retrieved the value of the koefisiensi correlation of 0,867 (very strong). Based on the correlation or relationship between indicators and 4ICU Webometrics rating, backlinks and the number of scientific publications is a factor that affects the ranking.